The Effectiveness of Preventive Maintenance in Overcoming Production Process Constraints on the Komori Lithrone G37 Offset Machine at PT X: Effectiveness of Preventive Maintenance in Overcoming Production Process Constraints on the Komori Lithrone G37 Offset Machine at PT X - Santoso, Habibi; Destyadhi Tri Wibowo (P3M Politeknik Negeri Media Kreatif, 2025)
Obstacles to damage that occur to the machine, not only cause problems with the machine but also affect the achievement of production targets, such as what happened to the Komori Lithrone G37 offset machine which experienced problems in the production process of book A in the 6000 print process 9 times machine problems occurred, book B in the 4000 print process 10 times machine problems occurred. Obstacles that occur such as weak wind pressure, sensor constraints. Preventive maintenance optimisation is the solution. The research method carried out is observation and on the machine and analysis. The results of this study, after preventive maintenance the production results are better and register and no more print problems occur on the machine